2016
DOI: 10.1080/13854046.2016.1190404
|View full text |Cite
|
Sign up to set email alerts
|

Everyday functioning and cognitive correlates in healthy older adults with subjective cognitive concerns

Abstract: Objective Few studies have examined functional abilities and complaints in healthy older adults with subjective cognitive concerns (SCC). The aims of this study were to assess everyday functioning in healthy older adults reporting high and low amounts of SCC, and examine cognitive correlates of functional abilities. Method Twenty-six healthy older adults with high SCC, and 25 healthy older adults with low SCC, as well as their knowledgeable informants completed the Instrumental Activities of Daily Living-Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 73 publications
4
36
0
2
Order By: Relevance
“…Initially, such findings may seem to run counter to most traditional models of symptom development associated with neurodegenerative diseases of aging in which cognitive deterioration, measured by conventional neuropsychological tests of these abilities, are expected to be evident before deterioration in everyday functioning. Our results, however, are consistent with a growing body of research suggesting that older adults who are seemingly cognitively normal may be able to detect subtle changes in their everyday functional abilities (for example, taking longer to complete complex IADLs or being prone to making more errors) before changes are evident on objective tests of neuropsychological function (Tomaszewski Farias et al, 2013; McAlister & Schmitter-Edgecombe, 2016). Our results are consistent with other previous studies that have shown that when subjectively reported functional changes are present in individuals who still perform within the normal range on cognitive tests, it substantially increases the risk they will develop frank cognitive impairment (i.e., MCI) in subsequent years (Amariglio et al, 2015).…”
Section: Discussionsupporting
confidence: 89%
“…Initially, such findings may seem to run counter to most traditional models of symptom development associated with neurodegenerative diseases of aging in which cognitive deterioration, measured by conventional neuropsychological tests of these abilities, are expected to be evident before deterioration in everyday functioning. Our results, however, are consistent with a growing body of research suggesting that older adults who are seemingly cognitively normal may be able to detect subtle changes in their everyday functional abilities (for example, taking longer to complete complex IADLs or being prone to making more errors) before changes are evident on objective tests of neuropsychological function (Tomaszewski Farias et al, 2013; McAlister & Schmitter-Edgecombe, 2016). Our results are consistent with other previous studies that have shown that when subjectively reported functional changes are present in individuals who still perform within the normal range on cognitive tests, it substantially increases the risk they will develop frank cognitive impairment (i.e., MCI) in subsequent years (Amariglio et al, 2015).…”
Section: Discussionsupporting
confidence: 89%
“…11 Another study found significant subtle functional changes, specifically in handling finances, self-management, and travel and event memory, in individuals with high subjective cognitive concerns. 9 Stogmann et al saw a decreased functional performance in SCD patients compared with controls. 12 Second, in longitudinal analyses, impaired IADL in SCD were associated with higher risk of MCI.…”
Section: Introductionmentioning
confidence: 98%
“…Ogata et al suggested self‐reported impaired higher‐level functional capacity in SCD in women, but not in men . Another study found significant subtle functional changes, specifically in handling finances, self‐management, and travel and event memory, in individuals with high subjective cognitive concerns . Stogmann et al saw a decreased functional performance in SCD patients compared with controls .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations